2018
DOI: 10.4314/bcse.v32i1.10
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and structural characterization of N-(2-{[(2E)-2-(2-hydroxybenzylidene)- hydrazinyl] carbonyl}-phenyl)benzamide (HL) and its Co(II), Fe(III), Cu(II) and Zn(II) complexes. X-ray crystal structure of HL

Abstract: ABSTRACT. N-(2-{[(2E)-2-(2-hydroxybenzylidene)hydrazinyl]carbonyl}phenyl)benzamide (HL) and itsCo(II), Fe(III), Cu(II) and Zn(II) perchlorate complexes were synthesized. The structures of HL and its complexes were confirmed on the basis of elemental analysis and FT-IR, FT-Raman, 1 H-NMR spectra. TGA, magnetic moment and molar conductivity measurements were carried out for the complexes. In addition, the crystal structure of HL was determined by X-ray diffraction at room temperature. It crystallizes in the mono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…The Cu(II) complex fits the spin value of 1.73 B.M. indicating an octahedrald 9 -system [26,33,[36][37][38].…”
Section: Magnetic Measurementsmentioning
confidence: 75%
“…The Cu(II) complex fits the spin value of 1.73 B.M. indicating an octahedrald 9 -system [26,33,[36][37][38].…”
Section: Magnetic Measurementsmentioning
confidence: 75%
“…The same results were confirmed by the IR spectroscopy. The signal at 8-9 ppm were assigned to imine proton (HC=N) is not flanked by satellites, this is an indicating that the N atom is not coordinated to tin(IV) [26]. The lack of down field shift in the position of the signal attributable to S-CH 3 (δ 2.55-2.57 ppm in free ligand) indicates no participitation of the -C=S group in binding [27].…”
Section: Infrared Spectramentioning
confidence: 96%
“…From the spectra of crude Eucalyptus lenceoleta and extractive free straw it is confirmed that lignin is present in these samples due to the absorption at 1514 and 1604 cm -1 . The (C-O) group stretching bands were observed at 1150, 1172 and 1188 cm -1 [26,27].…”
Section: Ft-ir Analysismentioning
confidence: 99%